How Are Adolescents Sleeping? Adolescent Sleep Patterns and Sociodemographic Differences in 24 European and North American Countries - Gariepy, Genevieve; Danna, Sofia; Gobiņa, Inese; Rasmussen, Mette; Gaspar de Matos, Margarida; Tynjälä, Jorma; Janssen, Ian; Kalman, Michal; Villeruša, Anita; Husarova, Daniela; Brooks, Fiona; Elgar, Frank J; et al. (The Journal of adolescent health, 2020)
PURPOSE: Insufficient and poor sleep patterns are common among adolescents worldwide. Up to now, the evidence on adolescent sleep has been mostly informed by country-specific studies that used different measures and age groups, making direct comparisons difficult. Cross-national data on adolescent sleep that could inform nations and international discussions are lacking. We examined the sleep patterns of adolescents across 24 countries and by gender, age, and affluence groups. METHODS: We obtained sleep data on 165,793 adolescents (mean age 13.5 years; 50.5% girls) in 24 European and North American countries from the recent cross-sectional Health Behaviour in School-aged Children surveys (2013-2014 and 2017-2018). For each country, we calculated the age-standardized mean in sleep duration, timing, and consistency and the proportions meeting sleep recommendations on school and nonschool days from self-reported bedtimes and wake times. We conducted stratified analyses by gender, age, and family affluence group. RESULTS: Adolescent sleep patterns varied cross-nationally. The average sleep duration ranged between 7:47 and 9:07 hours on school days and between 9:31 and 10:22 hours on nonschool days, and the proportion of adolescents meeting sleep recommendations ranged between 32% and 86% on school days and between 79% and 92% on nonschool days. Sleep patterns by gender and affluence groups were largely similar, but older adolescents slept less and went to bed later on school days than younger adolescents in all countries. CONCLUSIONS: The sleep patterns of adolescents vary across countries and sociodemographic groups. Insufficient sleep on school days is common in many countries. Public health and policy efforts to promote healthy adolescent sleep are encouraged.
Keywords: společenská třída; Cross-Sectional Studies; Adolescents; chování mladistvých; srovnání kultur; spánek; psychický stres; Cross-Cultural Comparison; Europe; Age disparities; mladiství; Social Class; Socioeconomic Factors; Public Health; Socioeconomic differences; Evropa; školy; průzkumy a dotazníky; United States; Sleep; průřezové studie; spánková deprivace; Stress, Psychological; dítě; Child; Schools; věkové faktory; International surveys; socioekonomické faktory; Sleep patterns; ženské pohlaví; Humans; Spojené státy americké; Surveys and Questionnaires; Sleep Deprivation; Adolescent Behavior; Age Factors; Female; veřejné zdravotnictví; Adolescent; Epidemiology; lidé